Keterlibatan Australia dalam Perang Pasifik & Pengaruhnya terhadap Kehidupan Politik Ekonomi Australia (1941-1945) - Adillah, Putry Maharani; Ribawati, Eko (As-Syirkah: Islamic Economic & Financial Journal, 2024)
Australia was involved in the Pacific War that occurred in 1941-1945 together with England, America and the Netherlands. The countries joined in the Allies against Japan. The occurrence of the Pacific War had effects on Australia’s political and economic life. This study aimed to investigate: (1) the Pacific War; (2) Australiain the Pacific War; (3) the effects of the Pacific War on Australia’s political and economic life. The study used Kuntowijoyo’s historical research method consisting of several stages. The first stage was to determine the research topic. The second stage was heuristics or collection of sources. The third stage was source verification or criticism. The fourth stage was interpretation or the process of interpreting the historical facts found. The last stage was historiography or history writing. The results of the study were as follows. (1) The Pacific War was the war of Japan against the Allies in the Pacific region. Japan was defeated by the Allies in the battle of the Coral Sea and then surrendered to the Allies on 14 August 1945. (2) In the Pacific War Australia was a strategic place for the American defense. Australia and America worked together against Japan, and Australia made the Solomon Islands as a bulwark to prevent Japan from ruling Australia. (3) The effect of the Pacific War on Australia’s political life resulted in a mixed political style combining British institutions and traditions with America-inspired federal structures. The effect of the Pacific War on Australia’s economic life was that agriculture was considered to have low productivity and was replaced by manufacturing industry.